Employer branding implementation and human resource management in Greek telecommunication industry - Antonios Kargas; Alexios Tsokos (Administrative Sciences, 2020)
Even though employer branding has its origins back to the 1990s, only after 2001 did it become a hot topic for human resource (HR) management. Ever since, a series of researchers and professionals have made an effort to understand how the image that job seekers have about employers is shaped and what benefits arise from this bilateral relationship. The Greek business environment delayed adoption of the most recently developed HR techniques, as a result of the economic crisis, and resulting decrease in working manpower, as well as budget reductions for HR. Only in the past few years have some of the leading companies in several business sectors started to implement employer branding as part of their corporate strategy. The current study aims to present how employer branding is actually under implementation in one of the most dynamic, national sectors-the telecommunication industry. Interviews in HR departments were conducted in order to collect (a) qualitative information regarding how employer branding is perceived and what results are expected from its implementation, as well as (b) quantitative data regarding its usefulness on attracting and choosing candidates, as well as evaluating existing employees. Results indicate that even though employer branding implementation is still an ongoing procedure, it has already started to transform HR departments' operational logic.
Keywords: 350; human resource management; employer branding; telecommunication companies; organizational culture; evaluating employees; attract candidates